2016
DOI: 10.3389/fmicb.2016.01599
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Global Epidemiology of Methicillin-Resistant Staphylococcus pseudintermedius: Inference of Population Structure from Multilocus Sequence Typing Data

Abstract: Background and rationale: Methicillin-resistant Staphylococcus pseudintermedius (MRSP) is a major cause of infections in dogs, also posing a zoonotic risk to humans. This systematic review aimed to determine the global epidemiology of MRSP and provide new insights into the population structure of this important veterinary pathogen.Methodology: Web of Science was searched systematically for articles reporting data on multilocus sequence typing (MLST) of S. pseudintermedius isolates from dogs or other animal or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
116
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(132 citation statements)
references
References 96 publications
14
116
0
2
Order By: Relevance
“…ST 71 was highly resistant to antibiotics, showing multiple resistances against commonly veterinary-licensed antibiotics (e.g., tetracyclines). On the other hand, ST 258 was reported to be more frequently susceptible to antibiotics (e.g., enrofloxacin, gentamicin) [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…ST 71 was highly resistant to antibiotics, showing multiple resistances against commonly veterinary-licensed antibiotics (e.g., tetracyclines). On the other hand, ST 258 was reported to be more frequently susceptible to antibiotics (e.g., enrofloxacin, gentamicin) [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, approximately 80% of the strains do not show any sensitivity to trimethoprim + sufonamide. Similarly to CC71, it is sensitive to amikacin (approximately 2% of resistant strains) [42]. Currently, a greater diversity in the occurrence of MRSP clonal complexes in a given area of the world can be observed and similarly to the USA, both CC68 and CC71, as well as CC84 are found.…”
Section: Antibiotic Resistance Of Staphylococcimentioning
confidence: 99%
“…Currently, a greater diversity in the occurrence of MRSP clonal complexes in a given area of the world can be observed and similarly to the USA, both CC68 and CC71, as well as CC84 are found. However, different profiles of antibiotic resistance of the strains of a given clonal complex found on different continents are noticed [11,42,60,68]. In Poland, the research conducted by Kizerwetter-Świda et al demonstrated that among the MRSP, ST71 strains with type II-III SCCmec dominated up to 2015.…”
Section: Antibiotic Resistance Of Staphylococcimentioning
confidence: 99%
See 2 more Smart Citations